Increasing days on feed for heavy short-fed yearling stocker cattle improves carcass characteristics - Stickel, A.; Houser, Terry A.; Olson, K. C.; Gerlach, B.; Goehring, B.; Pacheco, A.; Macek, M.; Parsons, G.; Miller, K.; Thompson, L.K.; Dikeman, Michael E.; Unruh, John A.; et al. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2011)
With increasing feed costs, producers may be able to utilize forage resources to help cattle gain weight before entering a high-concentrate finishing phase. In theory, heavy stocker cattle need less time on feed before slaughter compared to lighter weight cattle; however, research determining the impact of a short feeding system on product quality is limited. Therefore, the purpose of this research was to investigate the impact of a shortened, high-concentrate feeding period on carcass characteristics and meat quality traits of heavy yearling stocker cattle.
Beef Cattle Research, 2011 is known as Cattlemen’s Day, 2011
Keywords: Beef; Stocker cattle; Carcass characteristics; Performance; Dried distillers grains